The psychology of sport injury : from risk to retirement - Gledhill, Adam; Forsdyke, Dale (London Routledge, 2021)
"The Psychology of Sports Injury: From Risk to Retirement provides a critical overview of the psychology of sports injury, covering the 5Rs of sports injury: risk, response, rehabilitation, return to sport, and retirement. Drawing on a range of expert international perspectives from the fields of sport psychology and sport and exercise medicine, The Psychology of Sports Injury covers the psychological considerations associated with sports injuries, prior to the onset of injury through to supporting athletes with post-injury retirement. In addition to this injury lifespan perspective, the book features special interest topics including anterior cruciate ligament injury, sport-related concussion, spinal cord injury and the role of coaches in achieving athlete and team medical outcomes. Additionally, case studies provide the opportunity to apply learning from each chapter. By covering the sports injury journey from risk factors to retirement and including athlete mental health during sports injury, The Psychology of Sports Injury is an essential text for students, instructors, and practitioners in sports psychology, sport and exercise medicine, and other related fields"--
Includes bibliographical references and index.
Keywords: Sports injuries--Psychological aspects